Resistive switching in HfO2-x/La0.67Sr0.33MnO3 heterostructures: an intriguing case of low H-field susceptibility of an E-field controlled active interface - Antad, Vivek; Shaikh, Parvez A.; Biswas, Abhijit; Rajput, Shatruhan Singh; Deo, Shrinivas; Shelke, V, Manjusha; Patil, Shivprasad; Ogale, Satishchandra (ACS Applied Materials & Interfaces, 2021)
High-performance nonvolatile resistive random access memories (ReRAMs) and their small stimuli control are of immense interest for high-speed computation and big-data processing in the emerging Internet of Things (IoT) arena. Here, we examine the resistive switching (RS) behavior in growth-controlled HfO2/La0.67Sr0.33MnO3 (LSMO) heterostructures and their tunability in a low magnetic field. It is demonstrated that oxygen-deficient HfO2 films show bipolar switching with a high on/off ratio, stable retention, as well as good endurance owing to the orthorhombic-rich phase constitution and charge (de)trapping-enabled Schottky-type conduction. Most importantly, we have demonstrated that RS can be tuned by a very low externally applied magnetic field (similar to 0-30 mT). Remarkably, application of a magnetic field of 30 mT causes RS to be fully quenched and frozen in the high resistive state (HRS) even after the removal of the magnetic field. However, the quenched state could be resurrected by applying a higher bias voltage than the one for initial switching. This is argued to be a consequence of the electronically and ionically ``active'' nature of the HfO2-x/LSMO interface on both sides and its susceptibility to the electric and low magnetic field effects. This result could pave the way for new designs of interface-engineered high-performance oxitronic ReRAM devices.
Keywords: charge trapping-detrapping; low external magnetic field; oxide-oxide interface; pulsed laser deposition; resistive switching; Schottky barrier